2022
DOI: 10.3390/antiox11081539
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Isoforms in COPD Patients and Acute Cigarette Smoke-Exposed Mice: Induction of Oxidative Stress and Lung Inflammation

Abstract: Cigarette smoke (CS) is a major risk factor for chronic obstructive pulmonary disease (COPD), which represents the third leading cause of death worldwide. CS induces reactive oxygen species (ROS) production, leading to pulmonary inflammation and remodeling. NADPH oxidases (NOXs) represent essential sources of ROS production in the cardiovascular system. Whether and how NOX isoforms are activated in COPD patients and in response to acute cigarette smoke (ACS) remains incompletely understood. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…However, the exact mechanism underlying this phenomenon remains unclear, possibly attributed to the leakage of various proin ammatory markers from the lungs into the bloodstream. These ndings provide evidence for the presence of a systemic in ammatory response in individuals with COPD [44,45] .…”
Section: Discussionmentioning
confidence: 59%
“…However, the exact mechanism underlying this phenomenon remains unclear, possibly attributed to the leakage of various proin ammatory markers from the lungs into the bloodstream. These ndings provide evidence for the presence of a systemic in ammatory response in individuals with COPD [44,45] .…”
Section: Discussionmentioning
confidence: 59%
“…Consistent findings have been reported in isolated organ studies, with CS shown to stimulate NOX-dependent ROS production in isolated rat artery [ 123 ]. Evidence from animal studies has corroborated increased NOX activity with elevated basal ROS levels in lung tissue and bronchoalveolar lavage fluid (BALF) cells from CS-exposed mice [ 113 , 124 , 125 ]. These elevations were mitigated by conditional knockdown of NOX1, 2, and 4, and deletion of NOX2.…”
Section: The Ways How Cs Imposes Ros Burden On the Biological Systemsmentioning
confidence: 99%
“…39 Similarly, while all NOX isoforms are upregulated in lung tissue sections of patients with COPD, knockdown of NOX4 was more effective at reducing p-p65 expression and downstream TNF-α production in cigarette smoke-exposed mice. 40 Therefore, NOX4 is likely a significant contributor to lung disease progression and may be the main producer of ROS in lung conditions. Though we saw increases in NOX4, we did not observe changes in NT which may be due to the lack of change in NO metabolites in the lung.…”
Section: Paper Food and Functionmentioning
confidence: 99%